Multi-objective Finite-Domain Constraint-Based Forest Management - Eloy, Eduardo (2023)
This paper describes an implementation of a Constraint Programming approach to the problem of multi-criteria forest management optimization. The goal is to decide when to harvest each forest unit while striving to optimize several criteria under spatial restrictions. With a large number of management units, the optimization problem becomes computationally intractable. We propose an approach for deriving a set of efficient solutions for the entire region. The proposed methodology was tested for Vale do Sousa region in the North of Portugal.